Effect of Nd Substitution on the Microstructural and Dielectric Properties of Polycrystalline Ca(Ti0.5Fe0.5)O3 - Shah, MR; Amin, MR; Hossain, AKM Akther (Dhaka University Journal of Science, 2013)
Neodymium substituted calcium iron titanate having the general formula Ca1-xNdx(Ti0.5Fe0.5)O3 were prepared by the standard solid state reaction technique at relatively higher temperature (1473 K). X-ray diffraction (XRD) and optical microscopy are used to carry out the structural analysis and surface morphology, respectively. The XRD analysis confirms that all compositions are single phase orthorhombic in structure. The lattice parameters and the average grain size are found to decrease but the density to increase with the increase in Nd content. The dielectric constant (?/), dielectric loss (tan?) and ac conductivity (?ac) are studied at room temperature as a function of frequency and compositions. The room temperature ?/ is found to decrease with the increase in frequency and Nd content. On the other hand, the tan? and ?ac are observed to increase with the increase in frequency and decrease with the increase in Nd content. Dhaka Univ. J. Sci. 61(1): 125-129, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15113